Main Trends and Directions of External Migration - Salimov Sherzod Yunusovich (Research Parks Publishers, 2025)
This study takes into account these macroeconomic conditions, but focus is shifted to the reasons for the change in migration processes in terms of poorly understood sociocultural factors that affect foreign labor migration and reintegration of labor migrants in Uzbekistan. The article is based on reports from specialized studies of foreign labor migration and employment conducted by the Ministry of Employment and Labor Relations of Uzbekistan, publications of studies by international organizations, and data from indepth interviews with migrants and their families. The research revealed that under the influence of macroeconomic conditions, the change in the sociocultural context in 2006–2019 contributed to expansion of the geography of migration flows from Uzbekistan, the emergence of such phenomena as the “feminization” of migration and its “rejuvenation” against the background of certain elements of egalitarianism in an initially patriarchal society.